METODE KONTEMPORER MENGGALI OTENTISITAS HADIS ( KAJIAN PEMIKIRAN HARALD MOTZKI ) - Wazna, Ruhama (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
This article aims to describe the methods used by Harald Motzki in exploring the authenticity of the hadith. Since the 19th century scientifically, orientalists began to study the authenticity of hadith as a source of Islamic teachings, skeptical attitude of some orientalists get challenges from Muslim thinkers and some other orientalis. For Motzki, the two camps have not answered the substance of the question of authenticity of the hadith itself, he also uses certain methods in answering this. This article is a library of research with qualitative data collection and normative-theological approach of analyzing the truth of hadith which can be proven empirically and experimentally. The results show that, Motzki managed to prove authentic Hadith of the Prophet since the first century. Using Musannaf 'Abd al-Razzaq as the sample and the theory of dating and isnad cum matn analysis, he undermines the theories of his predecessor's hadith skepticism.